Analysis, Design and Fabrication of a Square Slot Loaded (SSL) Millimeter-Wave Patch Antenna Array for 5G Applications - Aghoutane, Bilal; Das, Sudipta; El Faylali, Hanan; Madhav, B. T. P.; El Ghzaoui, Mohammed; El Alami, Ali (Journal of circuits, systems, and computers, 2021)
A new compact 1 × 4 microstrip patch antenna array design for future 5G applications is presented in this paper. The proposed antenna array consists of square slot loaded with four radiating patch elements. The corporate feed network has been implemented for the excitation of the array. The feed line is connected to the square slot patch through a quarter-wave transformer matching network. The proposed array is designed on an FR-4 substrate with a dielectric constant of 4.4, thickness of 1.6 mm and loss tangent (tan δ ) of 0.02. It has a compact dimension of 9.590 × 17.802 × 1 . 6 m m 3 . The proposed structure has been designed and simulated by using commercially available HFSS software. The simulated results (reflection coefficient, gain, efficiency, radiation pattern) are verified through the measurement process to confirm the validity of the design concept. The measurement results are in good agreement with the simulated results. The proposed structure resonates at 38.1 GHz with a − 10 dB impedance bandwidth of about 3700 MHz (36.5 GHz to 40.2 GHz). The reflection coefficient at 38.1 GHz is − 34 dB, with a maximum gain of 7.81 dB. The proposed square slot loaded patch antenna array is very promising for 5G communications at 38 GHz band (37–40 GHz).